Molecular systematics, biogeography, and colony fusion in the European dry-wood termites Kalotermes spp. (Blattodea, Termitoidae, Kalotermitidae). Issue 4 (26th October 2017) - Scicchitano, V.; Dedeine, F.; Mantovani, B.; Luchetti, A.
Abstract: European dry-wood termites belong to the genus Kalotermes (Kalotermitidae), one of the two termite genera in Europe. Until the recent description of two new species, Kalotermes italicus in Italy and Kalotermes phoenicae in the eastern Mediterranean area, Kalotermes flavicollis was the only taxon known in this region. The presence of additional entities, suggested by morphological and physiological variation observed in K. flavicollis, was supported by molecular studies revealing four distinct genetic lineages: lineage A, K. flavicollis sensu strictu, from the Aegean area to Italy; lineage B, in Tuscany; lineage SC, in Sardinia and Corsica; lineage SF, in southern France. Lineages A and B may form mixed colonies, suggesting hybridization. To draw a more detailed picture of Kalotermes evolution and biogeography in Europe, we analyzed samples from previously unsampled areas, such as Spain and southern Italy, by means of the highly informative cox1/trnL/cox2 mitochondrial DNA marker. Overall, phylogenetic analyses confirmed previously identified lineages and taxa, but widened the distribution of the lineage SC to the mainland and of the lineage SF to Spain and Portugal. Results further provided evidence for the synonymy between lineage B and K. italicus . Species delimitation analysis suggested that the three K. flavicollis lineages, as well as K. italicus, can be separate taxa. Data also suggest a possible interspecific hybridization between K. italicus and both K. flavicollis lineages A and SC.